2020
DOI: 10.1007/s00018-020-03699-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a regulates insulin sensitivity via NPR3

Abstract: The pathogenesis of obesity-related metabolic diseases has been linked to the inflammation of white adipose tissue (WAT), but the molecular interconnections are still not fully understood. MiR-146a controls inflammatory processes by suppressing pro-inflammatory signaling pathways. The aim of this study was to characterize the role of miR-146a in obesity and insulin resistance. MiR-146a−/− mice were subjected to a high-fat diet followed by metabolic tests and WAT transcriptomics. Gain- and loss-of-function stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
(90 reference statements)
3
22
0
1
Order By: Relevance
“…The abnormal level of miR-21 and miR-146a has been observed both in normal aging and in the major ARDs [14,15]. In both mice model and observational studies in humans, miR-21 and miR-146a expression levels were consistently associated with both obesity and T2DM [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal level of miR-21 and miR-146a has been observed both in normal aging and in the major ARDs [14,15]. In both mice model and observational studies in humans, miR-21 and miR-146a expression levels were consistently associated with both obesity and T2DM [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggested that miR-146a −/− mice exposed to a high-fat diet gained more body weight and fat mass than controls, accompanied by insulin resistance and glucose intolerance. Both adipocytes transfected with miR146a and knockout of natriuretic peptide receptor 3 (NPR3), a target gene of miR-146a, exhibited an increase in insulin-stimulated glucose intake, demonstrating that miR-146a modulated insulin sensitivity by downregulating NPR3 [86]. These results indicated miR-146a might serve as a more promising biomarker to evaluate response to antidiabetic intervention than miR-126.…”
Section: Depression and Anxietymentioning
confidence: 97%
“…Modulates IFN signaling Garg et al 2021. [ 326 ] Chow and Salmena,2020 [303 Soni et al 2021 [ 306 ] Wyler et al 2021 [ 305 ] Wang etal 2010[ 286] Hsa-mir-146a Decreased in obesity and T2D Modulates insulin sensitivity Negative regulator of inflammation in adipose tissue Negatively regulates NF-kB by repressing IRAK-1 and TRAFb signaling Roos et al 2020 [ 313 ] Sanada etal 2020 [ 314 ] Decreased in serum of COVID-19 patients Anti-inflammatory COVID-19 patients with its lower levels responded poorly to anti-inflammatory treatment Targets SARS-CoV2 genome Desjarlais et al 2020 [ 315 ] Roganovic et al 2020 [ 316 ] Mirzaei et al 2020 [ 309 ] Sabbatinelli et al 2020 [ 308 ] Hsa-mir-17-5p Downregulated in omental fat and reduced in circulation in obesity Heneghan et al 2011 [ 279 ] Decreased in omental fat,PBMC, and circulation in COVID-19 antiviral Tsubota et al 2014 [ 311 ] Khan et al 2020 [ 304 ] Hsa-mir200-c-3p Downregulated in Adipose tissue, Repressed by leptin Decrease can increase ace2 expression Iacomino &S iani 2017 [ 270 ] Chang et al 2015 ] 319] Decreased in infection Modulation of target ACE2 in respiratory cells Liu et al 2017 [ 320 ] Hsa-mir-98-5p Decreased levels in T2D and obesity Kokkinopoulo et al 2019 [ 420] Modulation of TMPRSS2 expression Mirzaei et al 2020 [ 309 ] Hsa-Let-7a/ Let-7f Downregulated in obesity. Influence glucose metabolism and insulin sensitivity …”
Section: Why Is Obesity a Risk For Covid-19 ?—Pathways And Molecular ...mentioning
confidence: 99%